Exploring the relationship between the commuting experience and hedonic and eudaimonic well-being. (October 2021) - Liu, Qihao; Chen, Chia-Lin; Cao, Mengqiu
Highlights: We examine the relationship between the commuting experience and eudaimonic well-being. Educational attainment is related to hedonic well-being. Individual characteristics are related to the commuting experience and hedonic well-being. Travelling by public transport, walking and cycling can improve eudaimonic well-being. Ways of measuring the commuting experience, hedonic and eudaimonic well-being are discussed. Abstract: Studies linking commuting and well-being have received increasing attention in the field of mobility and transport. However, most studies primarily focus on the relationship between commuting and hedonic well-being. Few studies have investigated the commuting experience and eudaimonic well-being. Therefore, the aim of this paper is to explore the relationship between the commuting experience and both hedonic and eudaimonic well-being, using Heze (China) as a case study. The results indicate that, first, educational attainment is related to hedonic well-being, and transport mode is related to both the commuting experience and hedonic well-being. Furthermore, we found that some combinations of individual characteristics and transport mode are related to the commuting experience and hedonic well-being, but none of them relates to eudaimonic well-being. In addition, there are strong positive correlations between the commuting experience and hedonic well-being, between the commuting experience and eudaimonic well-being, and between hedonic and eudaimonic well-being. We also found that commuting by public transport, walking and cycling is more likely to improve the quality of the commuting experience, and both hedonic and eudaimonic well-being. In terms of policy implications, policymakers and transport planners should, therefore, promote people's well-being by prioritising the development of sustainable transport, and encouraging greater use of public transport and active travel.